USING ROLE-PLAYING TO PROMOTE HEALTH EDUCATION: EXPERIENCE REPORT ABOUT APPROACHING CHILDREN AGED 8 TO 12 YEARS OLD ABOUT SALMONELLOSIS - Bezerra Segundo, Willams Germano; Honfi, Sarah Rabelo; Almeida, Gabrielle Videres Alves de; Costa, Igor Souza Pessoa da; Maia, Ana Karina Holanda Leite; Mota, Clélia de Alencar Xavier (Revista de Ciências da Saúde Nova Esperança, 2018)
Salmonellosis is one of the most frequent zoonoses in human beings and has become a public health issue. The enterobacteria infections are one of the main debilitating factors in the population, frequently associated with chronic diarrhea and malnutrition, impairing physical and intellectual development, especially at younger ages. The need of simple measures of health education is notorious, such as washing hands and food, usage of footwear, general health interventions, which lead to the integration of the environmental, general and individual health habits, which are effective in fighting infections. Epidemiology indexes linked to disease outbreaks by food contamination are becoming higher by the year and there is a direct connection with poor hygiene standards. Therefore, aiming to alert the children, warn them about Enterobacteriaceae and teach about Salmonella in a playful way, a theatrical play was created bringing situations from daily life. Our subject, Salmonellosis, was approached using role-playing as a strategy, also using a costume from a cartoon character as a way of calling for children’s attention and therefore promote bonding with their group. The work targeted children, part of the population which have to be reached, mainly through games and drama, because with simple and accessible language mixed with creativity and humor their attention can be easily caught. Role-playing is a truly effective activity in promoting children’s learning, once playing opens room for thinking, so the child steps forward in reasoning, develops thinking, establish social interaction, understands the environment, satisfy desires, develops abilities, knowledge, and creativity. We can conclude through the promotion of this ludic action that, despite the great incidence of Salmonellosis in the population, prevention methods are still not well known. Through the performance of a play the main goal was reached, which was informing and bringing knowledge about Salmonellosis and prevention methods in a different way.